2021
DOI: 10.3389/fnhum.2021.646915
|View full text |Cite
|
Sign up to set email alerts
|

Subject-Independent Functional Near-Infrared Spectroscopy-Based Brain–Computer Interfaces Based on Convolutional Neural Networks

Abstract: Functional near-infrared spectroscopy (fNIRS) has attracted increasing attention in the field of brain–computer interfaces (BCIs) owing to their advantages such as non-invasiveness, user safety, affordability, and portability. However, fNIRS signals are highly subject-specific and have low test-retest reliability. Therefore, individual calibration sessions need to be employed before each use of fNIRS-based BCI to achieve a sufficiently high performance for practical BCI applications. In this study, we propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Since there were not enough trials of each condition per participant (22 trials) to train the classifier for each participant individually as above, we used the leave-one-participant-out cross-validation to train the LDA classifier. Leave-one-participant-out scheme gives participantindependent classifier performance on unseen data and is commonly used by several EEG and BCI studies such as Kwon and Im (2021) and Wu et al (2018). Thus, for each of the participants, a separate LDA classifier was trained for each sliding window as above with the feature vectors from corresponding windows from all the trials from the remaining 108 participants.…”
Section: Classification Of Single-trial Broadband Lrtc To Detect Movement and Motor Imagerymentioning
confidence: 99%
“…Since there were not enough trials of each condition per participant (22 trials) to train the classifier for each participant individually as above, we used the leave-one-participant-out cross-validation to train the LDA classifier. Leave-one-participant-out scheme gives participantindependent classifier performance on unseen data and is commonly used by several EEG and BCI studies such as Kwon and Im (2021) and Wu et al (2018). Thus, for each of the participants, a separate LDA classifier was trained for each sliding window as above with the feature vectors from corresponding windows from all the trials from the remaining 108 participants.…”
Section: Classification Of Single-trial Broadband Lrtc To Detect Movement and Motor Imagerymentioning
confidence: 99%
“…Through the competition, we have confirmed that the presented issues were appropriate for assessing advances in BCIs; nevertheless, several technical concerns remain. For example, many scholars have solved few-shot learning, domain generalization, and cross-session problems with high levels of performance in other disciplines (Seo et al, 2020;Zhou K. et al, 2020;Kim G. et al, 2021;Kwon and Im, 2021;Li et al, 2021). BCI systems using intuitive speech imagination, also compared to those that require the imagination of existing behavior or visual external stimuli, have been found to lack sufficient decoding performance (Cooney et al, 2018;Lee et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, selecting features relevant to the task will improve the classification performance. One advantage of CNN is the automatic extraction of discriminative features (Shajil et al, 2020 ; Kwon and Im, 2021 ). Learning hidden features and eliminating redundant information from the EEG signals will enhance the overall capability of BCI systems.…”
Section: Discussionmentioning
confidence: 99%
“…The pooling layer was inserted after the convolutional layer, to receive the compression feature map matrix from all selected channels and temporal values (Kwon and Im, 2021 ). The objective of the pooling layer is to improve the statistical efficiency of the network and improve its invariance (and subsequently its robustness).…”
Section: Methodsmentioning
confidence: 99%